Calidad en el servicio del Fondo de Cesantía del Magisterio Ecuatoriano del cantón Babahoyo - Torres Alvarez, Freddy Jazmani (2021)
This case study focused on determining the Quality in the Service of the Ecuadorian Teaching Unemployment Fund with the affiliates, this research has the quality variable, which will be analyzed throughout this research. The main objective of the research was to Analyze the Quality of the Service in the Ecuadorian Teaching Unemployment Fund company. The methodology used for this research was of a deductive-inductive type, which, because it was an evidential document of complex examination and because it was not very extensive, several opinions of users were taken, and the opinion of the object of study, in this case to the administration of said institution. As a result of this case study, several conclusions were obtained, being able to identify the anomalies that occur in the quality of service provided within the company, some of these conclusions focused on improving the processes so that there is a quality standard.